Strategy of implementing aerobic exercise as a pleiotropic effect in cancer patients with a history of administration cardiotoxic agents: a systematic review - Putu Yogi Pramana; Anak Agung Gede Kesuma Yudha (Journal of Indonesia Vascular Access, 2021)
The development of health science, with the discovery of a type of treatment to reduce mortality due to cancer, namely using chemotherapy agents such as anthracycline and trastuzumab. From the number of studies that have been done, the types of drugs such as anthracycline and trastuzumab have a cardiotoxic effect which is often associated with decreased heart-lung function and the incidence of cardiomyopathy. Exercise is reported to have a pleiotropic effect. Therefore, this study aims to synthesize evidence from the application of pleiotropic exercise in cancer patients undergoing chemotherapy with cardiotoxic agents. The search was performed according to the recommended reporting items for systematic review and meta-analyses (PRISMA). Obtained an accumulation of 2397 articles from PubMed and Google Scholar (2016-2020), which were assisted by the PICO search engine. The article was reviewed by the author within sorting using inclusion and exclusion criteria and obtained 28 articles accordingly. Aerobic exercise has pleiotropic effects by stimulating antioxidants and reducing reactive oxygen species (ROS) levels, reducing pro-apoptosis molecular signaling, stimulating myofilament, facilitating concentric cardia hypertrophy remodeling, and changing cardiac metabolism via adenosine monophosphate (amp) with kinase-mediated. Pretreatment aerobic exercise with minimal supervised 30-min exercise sessions 3 times/week for ≥12 weeks effectively reduce the risk of chemotherapy-induced cardiomyopathy (CRC). Aerobic exercise has a significant pleiotropic effect in patients undergoing chemotherapy with cardiotoxic agents.